Przestrzenna autokorelacja wybranych przyczyn zgonów w województwie śląskim w latach 2004-2006. Śląski Przegląd Statystyczny = Silesian Statistical Review, 2010, Nr 8 (14), s. 55-80 - Mielecka-Kubień, Zofia; Dziembała, Marek (Spatial autocorrelation of selected causes of deaths in Silesian Voivodeshipin the years 2004-2006, 2010)
In the last years, due to the development of spatial statistics and econometrics, as well as of geographic information system (GIS) and the availibility of statistical data, it became possible to conduct deepened research on spatial variation of deaths from different causes. In the paper differences in total and specific mortality rates, standardized according to age structure, among districts of Silesian Voivodeship, Poland, are studied, using the methods of spatial statistics; it is analysed whether they show spatial autocorrelation. It has been stated that the considered mortality rates show positive spatial autocorrelation. It is possible to distinquish clusters of districts of high and low values of the mortality rates. The worst situation, according to the considered causes of deaths, was observed in the big cities of the former Upper Silesian Industrial District and in the north-east part of the voivodeship. The best situation was found in the districts in the south-west part of the Silesian Voivodeship, and in the case of cancer mortality rates also in the north part. The results of the study confirm the usefulness of spatial statistics methods in the epidemiological research
Keywords: przyczyny umieralności; statystyka umieralności; causes of mortality; mortality statistics